The Hormetic Effects of a Brassica Water Extract Triggered Wheat Growth and Antioxidative Defense under Drought Stress - Abdul Khaliq; Muhammad Usman Ibrahim; Saddam Hussain; Muhammad Zia Ul Haq; Asma A. Al-Huqail; Muhammad Nawaz; Basharat Ali; Faheema Khan; Hyassam M. Ali; Manzer H. Siddiqui (Applied Sciences, 2022)
Drought is a major environmental constraint, affecting agricultural productivity worldwide. Allelopathic hormesis, the low-dose stimulatory effect of allelochemicals, offers a pragmatic solution in alleviating the adverse effects of drought in plants. This study, therefore, is conducted to evaluate the potential of a brassica water extract (BWE) in enhancing drought tolerance in wheat. The experiment was based on three factors, viz, drought with three levels (100%, 60% and 30% field capacity; FC), different concentrations of a brassica water extract (control, water spray, 0.5%, 1.0%, 1.5%, 2.0%, 2.5% and 3.0%) and two wheat cultivars, Ihsan-2016 (drought tolerant) and Galaxy-2013 (drought-sensitive). Drought stress, particularly at 30% FC, decreased the morpho-physiological attributes of both wheat cultivars; nevertheless, the application of brassica water extract, particularly at 2.0%, effectively enhanced tolerance against drought stress. Compared with the control, the application of 2.0% brassica water extract increased the morphological attributes, such as seedling length and the fresh and dry weights of both wheat cultivars in the range of 2–160% under 30% field capacity. In addition, the 2.0% brassica water extract triggered the activities of antioxidant enzymes, including superoxide dismutase, catalase and peroxidase (11–159%), decreased the hydrogen peroxide content (14–30%) and enhanced chlorophyll a and b and carotenoid contents (19–154%), as compared to the control, in both wheat cultivars under 30% field capacity. The vigorous growth and higher drought tolerance in wheat cultivars with brassica water extract application were related to improved chlorophyll contents and physiological attributes, a better antioxidant defense system and a reduced H2O2-based damaging effect.